Biodegradable mycelium tiles with elephant skin inspired texture for thermal regulation of buildings - Soh, Eugene (2024)
Climate change is one of the major environmental challenges of our time, with the energy used to heat or cool buildings a significant contributor. To improve thermal comfort, households install air conditioners, which consume energy. There is therefore an urgent need to find alternative passive solutions to cool down buildings. In this paper, inspiration is taken from elephants who cool themselves thanks to the wrinkles on their skin that limit heat gain, store water, and dissipate heat by evaporative cooling. To emulate this cooling, tiles with elephant skin inspired surface texture were designed. Experimental tiles were produced using mycelium, a biodegradable material grown by a fungus, Pleurotus ostreatus. These tiles are mycelium-bound composites (MBCs) where the fungus grows on bamboo microfibers, developing an interconnected network that binds the microfibers together. The introduction of the textured surface significantly improves the thermal response of the mycelium tiles as compared to the flat surface. The textured surface produces an anisotropic tile where the thermal properties of the tiles were measured for heating and cooling on both sides. The results show an improvement in the cooling rates by 25 % in the ‘up’ orientation and a reduction in heating rate by 2 %. In simulated rain conditions with the textured tiles, the cooling is further improved by 70 % as compared to dry conditions. The elephant-mycelium tiles therefore show promise for thermal regulation of buildings in hot climates.